Strategi Manajemen Kesan Pemandu Wisata dalam Meningkatkan Daya Tarik Wisata Galeri Lokananta - Restikanaya Sylvana Haryanti; Sidiq Setyawan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Lokananta Gallery is one of the historical tourist destinations in Solo City that has undergone revitalization to increase its appeal. One of the efforts made is the provision of tour guide services. However, this service still faces challenges, such as lack of attention from visitors and the diversity of tourist characteristics, which can hinder the effectiveness of information delivery. In this context, impression management strategies become important as an interpersonal communication approach that can shape tourists' positive perceptions of the tourism experience. This study aims to examine the impression management strategies used by tour guides in increasing the appeal of Lokananta Gallery. The method used is descriptive qualitative with a case study approach. Data were obtained through in-depth interviews with three tour guides, and analyzed using Erving Goffman's impression management theory. The results showed that tour guides implemented five impression management strategies, namely ingratiation (building closeness with visitors), self-promotion (showing personal competence), exemplification (showing dedication and positive values), supplication (creating a humble impression), and intimidation ceriagan (subtly showing authority). Implementing these strategies has been shown to help build a professional image of guides, increase enjoyable interactions, and strengthen visitors' positive impressions of the Lokananta Gallery.